Caracterização de superfícies texturizadas por vibração: análise de parâmetros de rugosidade e molhabilidade - Moraes, Alvaro Araujo de (Universidade Federal de São Carlos, 2026)
Surface engineering has become an essential field for understanding how topographical characteristics influence the functional performance of materials in different applications, such as heat exchangers. Therefore, investigating the relationship between manufacturing parameters, machining vibrations, and variations in surface roughness parameters has attracted increasing scientific and technological interest. In this context, vibrations induced by actuators or inherent to machining processes can significantly alter surface morphology, resulting in surfaces with distinct characteristics depending on the process conditions. Thus, the present work aims to characterize flat machined surfaces of aluminum, brass, and stainless steel produced through turning and milling processes under different machining conditions, with emphasis on the analysis of roughness and wettability parameters. The characterization of the surface topology of the samples was carried out using confocal microscopy, evaluating the parameters of average roughness (Ra), skewness (Rsk), and kurtosis (Rku). Wettability analyses were performed using an optical tensiometer, enabling measurements of static, advancing, and receding contact angles, with distilled water used as the working fluid. The results obtained from turning indicated that, for all analyzed materials, samples produced under more severe machining parameters exhibited higher contact angles compared to surfaces manufactured under milder conditions. In contrast, the opposite behavior was observed for aluminum samples produced by milling, where higher contact angle values were associated with the higher speed condition corresponding to unstable machining. Overall, a consistent association was observed between the behavior of the skewness parameter and static contact angles, since in several cases where skewness varied, variations in static contact angle were also observed. These results contribute to the understanding of the influence of vibrations on the topographical characteristics of machined surfaces, supporting the correlation between manufacturing conditions, surface roughness, and wettability.
Characterization of surfaces textured by vibration: analysis of roughness and wettability parameters
Keywords: Usinagem; Chatter; Ângulo de contato; Texturização de superfícies; Machining; Chatter; Contact angle; Surface engineering; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO; 9. Indústria, Inovação e Infraestrutura